Gene in the region of the Friedreich ataxia locus encodes a putative transmembrane protein expressed in the nervous system. - Duclos, F (1993)
Friedreich ataxia (FRDA) is an autosomal recessive degenerative disorder that affects the cerebellum, spinal cord, and peripheral nerves. The FRDA gene was localized in 9q13-q21 within 0.7 centimorgan of the D9S5 and D9S15 loci. One recently reported recombination event and haplotype analysis in a population with a founder effect suggested that the FRDA locus is on the D9S5 side. Using a conserved probe from the D9S5 locus, we have now identified an approximately 7-kilobase (kb) transcript and report cloning of its cDNA. The corresponding gene, X11, extends at least 80 kb in a direction opposite D9S15. The gene is expressed in the brain, including the cerebellum, but is not detectable in several nonneuronal tissues and cell lines. In situ hybridization of adult mouse brain sections showed prominant expression in the granular layer of the cerebellum. Expression was also found in the spinal cord. The cDNA contains an open reading frame encoding a 708-amino acid sequence that shows no significant similarity to other known proteins but contains a unique, 24-residue-long, putative transmembrane segment. On the basis of its genomic localization and its neuronal site of expression, particularly in the cerebellum, this "pioneer" gene represents a candidate for FRDA. Direct evidence of its involvement in FRDA will require a search for causative point mutations in patients.